The International Library of African Music - Tracey, Hugh (International Library of African Music, 1954)
A most important step forward in the research into African music has been made this year by the establishment in Africa of a library which is entirely devoted to the work of presenting pressed recordings, fully classified, for this special branch of African study.
Keywords: South Africa; Ethnomusicology; Music; Music libraries; Africa; Classification; History; Criticism; African Music